SCIENTIFIC ALTERNATIVES TO ANIMALS IN MEDICAL EXPERIMENTS - FARHANA R,; MENEZES GA, (International Journal of Pharma and Bio Sciences, 2013)
To assess the preference and acceptance of the scientific alternatives to animals in medical experiments in research. This questionnaire based study was conducted in Sree Balaji Medical College and Hospital, and Madras Institute of Technology (MIT), Chennai, Tamil Nadu, India. The numbers of participants were 100 and the questionnaire was based on Likert scale consisting of five ordered response level. The results were analyzed to find out the preference and acceptance of scientific alternatives to animals. Overall, 28% of the participants felt it is ethical to do animal experiment which benefits human beings but violates the rights of animals; 57% participants suggested alternative models like fruit flies, nematodes, zebra fish are less expensive, easy to handle and experimentally more efficient; 60% participants felt human volunteers could be used for microdosing as an important alternative and 73% participants recommended that animal experiments are necessary in medical exp. Further, 74% agreed with 3R’s (reduction, refinement and replacement) for performing animal experiments. Researchers concluded that animal experiment can be done keeping 3R’s in mind and also alternatives to animal testing would be desirable if funding is provided by the Government or any funding agency for the work on alternatives to animal testing.